2011
DOI: 10.5402/2011/707154
|View full text |Cite
|
Sign up to set email alerts
|

Extraluminal Colonic Carcinoma Invading into Kidney: A Case Report and Review of the Literature

Abstract: Renal metastasis from primary colon cancer is very rare, comprising less than 3% of secondary renal neoplasms. There are just 11 cases reported in the medical literature of colonic adenocarcinoma metastatic to the kidney. Of these cases, none occurred via direct invasion. We report a unique case of a 51-year-old female with extraluminal colonic adenocarcinoma which directly invaded into the kidney. Additionally, we investigate the causal relationship between the site of invasion and a previous stab injury by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Among eleven casereports within the medical literature of colonic adenocarcinoma metastatic to the kidney, none occurred via direct invasion (Ono et al, 2002). In the majority studies, result demonstrated that renal metastasis from primary colon cancer is very rare, except for a unique case-report of a 51-year-old female with extra luminal colonic adenocarcinoma that directly invaded the kidney (Nelson et al, 2011). The relationship between CRC and the impaired renal function showed an important diminution in 31(17%) patients (GFR < 60 ml/min/1.73m2).…”
Section: Discussionmentioning
confidence: 99%
“…Among eleven casereports within the medical literature of colonic adenocarcinoma metastatic to the kidney, none occurred via direct invasion (Ono et al, 2002). In the majority studies, result demonstrated that renal metastasis from primary colon cancer is very rare, except for a unique case-report of a 51-year-old female with extra luminal colonic adenocarcinoma that directly invaded the kidney (Nelson et al, 2011). The relationship between CRC and the impaired renal function showed an important diminution in 31(17%) patients (GFR < 60 ml/min/1.73m2).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal oncology, the presence of a horseshoe kidney previously resulted in conversion from laparoscopic to open resection . To our knowledge, no cases of direct invasion from a colorectal cancer into a pelvic kidney have been reported, possibly due to the barrier role of the Gerota's fascia and peritoneum . In our case, the pancake kidney resulted in difficult dissection, potentially increasing the risk of ureteric injury.…”
mentioning
confidence: 72%
“…Metastases to other organs, such as the kidney, have been reported in 2.7% of postmortem analyses, far rarer than that in clinical practice [ 15 , 16 ]. Because the kidneys are highly vascular organs, metastatic infiltration is often the result of arterial embolization or direct invasion [ 5 , 8 , 17 ]. Although cytoreduction surgery has been shown to benefit patients with CRC and soft tissue sarcomas, nephrectomy with curative intent in oligometastatic CRC to kidney remains controversial, mainly due to the absence of established guidelines for such specific groups of patients [ 7 , 8 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the most common site of CRC metastases [ 3 ]. Metastases in kidneys are rare, comprising less than 3% of secondary renal neoplasms [ 4 , 5 ]. Adrenal metastases from CRC occur at a rate ranging from 3.1 to 14.4%.…”
Section: Introductionmentioning
confidence: 99%